Prevalence of Complementary Feeding Indicators and Associated Factors Among 6- to 23-Month Breastfed Infants and Young Children in Poor Rural Areas of China - Liu, Jing; Huo, Junsheng; Sun, Jing; Huang, Jian; Gong, Weiyi; Wang, Ou (Frontiers in Public Health, 2021)
This study aimed to estimate the status of complementary feeding (CF) and its associated factors among 6- to 23-month breastfed infants and young children (IYC). We used secondary data from the China Nutrition Improvement Project on Children in Poor Areas in 2018. The status of complementary feeding was provided by IYC’ parents through 24-h dietary recall. The study included 13,972 6- to 23-month-old breastfed IYC comprising 24.7% 6-8-month, 28.5% 9-11-month, 31.4% 12-17-month and 18-23- month IYC. The highest percentage of IYC introduced to cereal foods was 84.8%. Nearly 83.6% of 6- to 8-month infants were introduced to solid or semi-solid food (ISSF). The prevalence of meeting requirements of non-dairy animal source food (NDASF), and minimum acceptable diet (MAD) was 75.3%, and 35.1% of 6- to 23-month IYC, respectively, and was significantly higher in older than younger IYC (p < 0.001). Age of IYC, education level of parents, paternal employment, and nutrition knowledge of parents were positively associated factors for the prevalence of meeting MAD requirements, and diarrhea at two weeks and maternal employment were negatively associated with MAD. Totally, the prevalence of meeting requirements of MAD was relatively lower in breastfed IYC. The government should scale up appropriate complementary feeding with consideration of food availability.